Rapid and Specific Detection of All Known Nipah virus Strains’ Sequences With Reverse Transcription-Loop-Mediated Isothermal Amplification - Ma, Liping; Chen, Zhen; Guan, Wuxiang; Chen, Quanjiao; Liu, Di (Frontiers in Microbiology, 2019)
Nipah virus (NiV) is a zoonotic virus and can be transmitted through contaminated food or directly between people. NiV is classified as a Biosafety Level 4 agent, not only because of its relatively high case fatality rate, but also because there is no vaccine or other medical countermeasures and it appears to be transmitted by fomites/particulates. The development of rapid detection assay for NiV is of great importance because no effective field test is currently available. In this study, an isothermal (65°C) reverse transcription-loop-mediated isothermal amplification (RT-LAMP) method was developed, targeting the nucleocapsid protein (N) gene, for the rapid detection of NiV, and was compared with conventional RT-PCR. Three pseudoviruses of NiV N gene representing all known strains were constructed to replace live NiV. A set of RT-LAMP primers, targeting a highly conserved region of the N gene in the viral genome was designed to identify all known NiV strains. Sensitivity tests indicated that the detection limit of the RT-LAMP assay was approximately 100 pg of total NiV pseudovirus RNA, which is at least 10-fold higher than that of conventional RT-PCR. Specificity tests showed that there was no cross-reactivity with nucleocapsid protein gene of Hendra virus, Newcastle disease virus, Japanese encephalitis virus, or Influenza A virus. The RT-LAMP assay provides results within 45 min, and requires no sophisticated instruments, except an isothermal water bath or metal bath with 1 μl calcein indicator. An analysis of the clinical samples showed that the assay had good stability. In conclusion, systematic experiments have shown that the RT-LAMP assay developed here effectively detects three NiV pseudoviruses representing all known strains of NiV, with high specificity, sensitivity and stability.